Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 125651 by Algoritm last updated on 12/Dec/20

Answered by Olaf last updated on 12/Dec/20

 { ((y_1 ′ = y_1 +4y_2  (1))),((y_2 ′ = −y_1 +y_2 +e^(3x)  (2))) :}  (2) : y_1  = y_2 −y_2 ′+e^(3x)  (3)  ⇒ y_1 ′ = y_2 ′−y_2 ′′+3e^(3x)     (1) y_2 ′−y_2 ′′+3e^(3x)  = y_2 −y_2 ′+e^(3x) +4y_2   y_2 ′′−2y_2 ′+5y_2  = 2e^(3x)   (E_H ) : y_(2H) ′′−2y_(2H) +5y_(2H)  = 0  r^2 −2r+5 = 0  r = ((2±4i)/2) = 1±2i  y_(2H)  = e^x (Acos2x+Bsin2x)  (E_0 ) : y_(2,0) ′′−2y_(2,0) +5y_(2,0)  = e^(3x)   y_(2,0)  = αe^(3x)   ⇒ 9α−2×3α+5α = 2  α = (1/4), y_(2,0)  = (e^(3x) /4)  y_2  = y_(2H) +y_(2,0)  = e^x (Acos2x+Bsin2x)+(e^(3x) /4)  ⇒ y_2 ′ = e^x [(A+2B)cos2x+(B−2A)sin2x]+((3e^(3x) )/4)  (3) : y_1  = −2e^x (Bcos2x−Asin2x)−(e^(3x) /2)

{y1=y1+4y2(1)y2=y1+y2+e3x(2)(2):y1=y2y2+e3x(3)y1=y2y2+3e3x(1)y2y2+3e3x=y2y2+e3x+4y2y22y2+5y2=2e3x(EH):y2H2y2H+5y2H=0r22r+5=0r=2±4i2=1±2iy2H=ex(Acos2x+Bsin2x)(E0):y2,02y2,0+5y2,0=e3xy2,0=αe3x9α2×3α+5α=2α=14,y2,0=e3x4y2=y2H+y2,0=ex(Acos2x+Bsin2x)+e3x4y2=ex[(A+2B)cos2x+(B2A)sin2x]+3e3x4(3):y1=2ex(Bcos2xAsin2x)e3x2

Terms of Service

Privacy Policy

Contact: info@tinkutara.com